A laboratory study to estimate the effectiveness of a number of pyrethroid pesticides as wheat grain protectors against three types of store pests. - Lubna Abbas (College of Education for Pure Sciences, 2009)
Abstract In laboratory evaluation of the parathyroid insecticides ALPHACHEM® ( %5 EC), DECIS® ( %20 EC) and TRUST® (%25 WP) as protestants for wheat against adults of red Tribalism castaneum, confused Tribalism confusum and longheaded Latheticus oryzae flour beetles, and the relative response to toxicities of the these insecticides were evaluated, according to The LC50 and LC95 values. Mortality was recorded at 24, 48 and 72 hrs. after exposure to wheat Triticum aestivum treated with different concentrations of the three insecticides. The LC50 and LC95 values varied with species and exposure period. The toxicity data obtained against the three species showed that, the adults of longheaded were generally more susceptible to the three insecticides than these of red and confused flour beetles. But, the adults of confused Tribalism confusum flour beetles were more tolerant to ALPHACEM at 24 hour post-exposure, and ALPHACEM and DECIS were more effective than TRUST. The toxicity of the three insecticides in general, increased as the exposure period increased.